Tissue-engineered endothelial cell layers on surface-modified Ti for inhibiting in vitro platelet adhesion - Wang, Xiupeng; He, Fupo; Li, Xia; Ito, Atsuo; Sogo, Yu; Maruyama, Osamu; Kosaka, Ryo; Ye, Jiandong (Science and technology of advanced materials, 2013)
A tissue-engineered endothelial layer was prepared by culturing endothelial cells on a fibroblast growth factor-2 (FGF-2)-l-ascorbic acid phosphate magnesium salt n-hydrate (AsMg)-apatite (Ap) coated titanium plate. The FGF-2-AsMg-Ap coated Ti plate was prepared by immersing a Ti plate in supersaturated calcium phosphate solutions supplemented with FGF-2 and AsMg. The FGF-2-AsMg-Ap layer on the Ti plate accelerated proliferation of human umbilical vein endothelial cells (HUVECs), and showed slightly higher, but not statistically significant, nitric oxide release from HUVECs than on as-prepared Ti. The endothelial layer maintained proper function of the endothelial cells and markedly inhibited in vitro platelet adhesion. The tissue-engineered endothelial layer formed on the FGF-2-AsMg-Ap layer is promising for ameliorating platelet activation and thrombus formation on cardiovascular implants.